Few Outflow Problems With a Self-locating Catheter for Peritoneal Dialysis: A Randomized Trial. Issue 48 (December 2015) - Stegmayr, Bernd G.; Sperker, Wolfgang; Nilsson, Christina H.; Degerman, Christina; Persson, Sven-Erik; Stenbaek, Jan; Arnerlöv, Conny
Abstract : Abstract: We developed a technique for direct start of peritoneal dialysis. Using a coiled or straight Tenckhoff catheter often results in obstruction of flow. A self-locating Wolfram catheter is on the market. It is not clarified if this results in a benefit. The primary aim of this study was to perform a randomized investigation to clarify if the use of a self-locating peritoneal dialysis (PD) catheter would result in different flow problems than a straight Tenckhoff catheter. A total of 61 insertions were made who were randomized and received either a straight Tenckhoff (n = 32) or a self-locating Wolfram catheter (n = 29). A previously described operation technique allowed immediate postoperative start of dialysis. Seven straight Tenckhoff catheters had to be changed into self-locating catheters, and none vice versa, due to flow problems ( P  = 0.011). An early leakage resulted in temporarily postponed PD in 4 patients. This study showed that using the present operation technique the self-locating PD-catheter causes fewer obstruction episodes than a straight Tenckhoff catheter. This facilitates immediate postoperative start of PD.